Tax avoidance as an anti-austerity issue: the progress of a protest issue through the public sphere - Birks, Jen (Sage, 2017)
Theorists of left and right agree that periods of crisis are fertile times at which to precipitate change. However, protesters on the periphery of the public sphere must overcome barriers, or what Habermas called ‘sluice gates’, if their discourse is to be publicly and politically influential. This study of newspaper discourse and activity in parliament and the public sphere over a six year period takes tax justice campaigning in the UK as a case study, and in particular protest group UK Uncut’s attempt to mobilize opposition to austerity by advocating a crackdown on tax avoidance as an alternative to cuts. It finds that whilst UK Uncut successfully amplified existing arguments previously raised by experts, trade unions and the left-leaning press, austerity barely figured in debate about tax avoidance once it was picked up by other actors in the public sphere on the other side of the 'sluice gates'. The reasons for this were structural and discursive, related to the role and interests of receptive actors at the institutional centre of the public sphere, and their ability, along with the conservative press, to transform the moral framing of tax avoidance from the injustice of making the poor pay for the financial crisis through cuts, into the 'unfairness' of middle class earners paying higher taxes than wealthier individuals and corporations. The latter reifies the 'hardworking taxpayer', and implies a more instrumental and clientalistic relationship to the state, and an essentially neoliberal sense of fairness. Where neoliberal ideology was challenged, it was in social conservative terms – nationalist opposition to globalisation, framing multinational corporations as a threat to the domestic high street – rather than protesters’ social democratic challenge to market power and social injustice. This indicates how a progressive message from the periphery can be co-opted into the currently resurgent right-wing populism.